Guyana : 2010 Article IV Consultation; Staff Report, Supplement, Public Information Notice on the Executive Board Discussion and Statement by the Executive Director for Guyana. (IMF Staff Country Reports; Country Report ;, 2011)
Despite external and domestic shocks, the Guyanese economy demonstrated resilience and registered a fifth consecutive year of robust growth in 2010. The authorities started making payouts to Colonial Life Insurance Company (CLICO) policyholders, in line with their plans to minimize fiscal costs. Efforts to improve the Guyana Revenue Authority (GRA) continued. Its new functional organization was consolidated, improving further the integrated tax information system (TRIPS), the profiling of taxpayers, and on-site inspections at the country's ports of entry. Executive Directors endorsed the authorities' Low Carbon Development Strategy.